2014
DOI: 10.2472/jsms.63.662
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fine Particle Peening on Surface Residual Stress of a TRIP-Aided Bainitic Ferrite Steel

Abstract: To apply a transformation-induced plasticity (TRIP)-aided steel consisting of bainitic ferrite structure matrix and metastable retained austenite of 10 vol% (TBF steel) to some precision gears, the effects of fine particle peening on the Vickers hardness and residual stress in a surface layer of the TBF steel were investigated. The peened surface layer showed much higher Vickers hardness and compressive residual stress than those of a quenched and tempered SNCM420 steel. The increased Vickers hardness was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The term f is a constant, b is the Burgers vector, and r denotes the mean diameter of the second-phase particles. Because the microstructure of TM steel is composed of a soft matrix (wide lath-martensite) and a hard second phase (MA-like phase), high compressive internal stress, which results from a difference in flow stresses between the matrix and the second phase, takes place in the matrix [28]. Figure 9 shows a typical fracture in TM steel (Steel A) after stretch forming, stretch flanging, and bending tests.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The term f is a constant, b is the Burgers vector, and r denotes the mean diameter of the second-phase particles. Because the microstructure of TM steel is composed of a soft matrix (wide lath-martensite) and a hard second phase (MA-like phase), high compressive internal stress, which results from a difference in flow stresses between the matrix and the second phase, takes place in the matrix [28]. Figure 9 shows a typical fracture in TM steel (Steel A) after stretch forming, stretch flanging, and bending tests.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…In particular, fine particle peening can enhance the fatigue strength by increase in surface hardening and the compressive residual stress, with a small surface roughness, which resulted from strain-induced martensite transformation of retained austenite [28,37]. …”
Section: Prospective Applicationsmentioning
confidence: 99%
“…Natori et al [27] proposed that residual stress resulting from the strain-induced martensitic transformation (ΔσXα,t) can be calculated using Equation (3),…”
Section: Steelmentioning
confidence: 99%
“…Many researchers found that shot peening considerably increases the fatigue strength of the conventional case-hardening martensitic steels [49][50][51][52][53][54][55][56][57][58][59]. Sugimoto et al [60][61][62] have reported that high fatigue strength and low notch-sensitivity for fatigue of the TM steel are achieved by fine-particle peening and/or vacuum carburization because of small surface roughness and the improved surface-hardened layer properties. In addition, they showed that further increase in fatigue limit of the steels is achieved by using of multi process of vacuum carburization and fine-particle peening which increases the hardness and residual stress in the surface hardened layer [63][64][65].…”
Section: Introductionmentioning
confidence: 99%